2012
DOI: 10.2106/jbjs.j.01348
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Brachii Long Head Overactivity Associated with Elbow Flexion Contracture in Brachial Plexus Birth Palsy

Abstract: Overactivity of the long head of the biceps brachii muscle is associated with and may contribute to the development of elbow flexion contracture in children with brachial plexus birth palsy. Elbow flexion contracture may not be associated with an elbow flexor-extensor muscle imbalance, as previously hypothesized. The negative impact of elbow flexion contracture on upper extremity function warrants future research in the development of preventive and therapeutic techniques to address elbow flexion contractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…10 On the other hand, Ballinger's and Hoffer's 6 suggestion that flexor weakness correlates with elbow flexion contracture severity is inconsistent with our results. A recent study 22 suggested single muscle overactivity as a factor: overactivity of the long head of the biceps was related to elbow flexion contractures based on EMG findings in older children (mean age 14 years). Our EMG findings are not precise enough to refute or support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, Ballinger's and Hoffer's 6 suggestion that flexor weakness correlates with elbow flexion contracture severity is inconsistent with our results. A recent study 22 suggested single muscle overactivity as a factor: overactivity of the long head of the biceps was related to elbow flexion contractures based on EMG findings in older children (mean age 14 years). Our EMG findings are not precise enough to refute or support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…48 Contracture is thought to be due to overactivity of the long head of the biceps brachii muscle serving as an additional anterior stabilizer of an abnormal glenohumeral joint. 49 Currently, the mainstays of treatment for elbow flexion contracture in children with BPBP are serial casting and nighttime splinting. A recently published treatment algorithm recommends serial casting for contractures of Z40 degrees and nighttime splinting for contractures of 20 to 40 degrees.…”
Section: Elbow Deformitymentioning
confidence: 99%
“…However, EFC occurs even in cases without recovery of elbow flexion [11]. Additional hypotheses include: long head of biceps over-activity [12], uncommon C8-T1 pattern injuries [13], presence of shoulder contracture [14], and abnormal posturing [10]. The uncertain aetiology is reflected in the range of proposed treatments: serial casts/splints [8], arthrodiastasis [15], anterior release [16], and muscle lengthening [17].…”
Section: Introductionmentioning
confidence: 99%